Sales Management Control Strategies in Banking Strategic Fit and Performance Impact - Mueller, Florian; SpringerLink (Online service). (Wiesbaden Gabler, 2011)
Not only have the global financial crisis, a changing regulatory environment, increasing competitive pressure, and changes in customer behavior created an overall difficult environment for banking institutions, but they have also increased the pressure on their sales performance. Based on the results of 300 interviews with sales executives of banks in Germany, Florian Mueller empirically investigates how retail, private, and corporate banking institutions need to set up their sales management control strategy in accordance to their specific environment, business strategy, and organizational characteristics in order to increase performance.
Banking in Germany; Strategy and Strategic Management; Sales Management Control; Internal and External Influencing Variables; Assessment of the Environmental Influence on Configurations; Investigation of the Performance of Configurations
Electronic reproduction.
Keywords: Bank management; Selling -- Banks and banking; Banks and banking -- Germany; Electronic books